SIMPLE SENTENCE IN GIVING THE TITTLE OF HEADLINE NEWS - Merina, Yola (Universitas PGRI Sumatera Barat, 2017)
This research investigates the structure of simple sentence which was used by journalist to convey the news to the reader. Moreover, this paper was performed to investigate the transitivity of simple sentence of the news tittle and also to know the constituent structure in simple sentence in declaring the news to the consumers of news, namely readers. The method of collecting data were performed in observational method with the following technique was non-participant observational technique. The data were taken only from headline news during one month. In analyzing the data, the writer used referential identity method which using equalizer technique as the following technique. The result of this paper showed the simple sentences which were used by journalist were nuclear constituent where the transitivity of sentences were constructed in active sentence and the part of transitive verbs for fulfilling predicate was also available.